Investment Decision Making for Alternative Fuel Public Transport Buses: The Case of Brisbane Transport - Patil, A.; Herder, P.; Brown, Kerry (Centre for Urban Transportation Research, University of South Florida, 2010)
Cleaner and less polluting public transport buses based on alternative fuels are of paramount importance if cities are to attain their ambitious emissions reduction targets. Public transport buses are high usage vehicles that operate in heavily congested areas where air quality improvements and reductions in public exposure to harmful air contaminants are critical. As such, they are good candidates for achieving both near-term and long-term emission reductions. Decision making for the investment in alternative fuel buses is dependent on future technological development and emissions standards, and it is difficult, given the uncertainty in regards to both these factors. The objective of this paper is to develop an analytical framework that will give us more insight into the trends in emissions standards as well as technology development, and eventually translate these insights into a sound investment decision making strategy. This paper concludes that, due to presence of uncertainties, the decision maker (public transport fleet manager) can take only incremental steps that will allow him or her to safeguard investments. Furthermore, if policy makers are serious about accelerating the diffusion of alternative fuels, they should aim at creating stable policy environment.